Eksplorasi Ekstrak Pewarna Alami Sebagai Bahan Pewarna Organik Untuk Tekstil Cetak - Syahida Nisa Abdurahman; Kahfiati Kahdar (JURNAL RUPA, 2021)
Environmental conservation and sustainable living were a movement that directed people to return to using eco-friendly materials, especially in creating textile products. One solution to the problem is to reduce textile waste made from synthetic materials by creating organic inks that can be an alternative ink in the textile printing process. This study used a qualitative approach and experimental methods through the exploratory phase of the extract solution of several natural dyes added with the thickener alginate, guar gum, and tapioca flour. The organic ink has been applied to textiles made from 100% cotton using a screen printing technique with a post-mordanting fixation process. This experiment aimed to determine the optimal results of the dye paste solution (organic ink) on absorption, fabric color, fading test, visual and texture results. The experimental results prove that color printing using eco-friendly materials with screen printing techniques can be applied to textiles. Each extract solution, thickening agent, and mordant substance on the fixation process have different absorption with the result that has been made varying colors and visual results on the textile surface.